Sketches of transition : an atlas on growth and decay. - Bazzoli, Michele (Onomatopee, 2023)
This volume brings together the practices of five different artists in relation to the key concept of transition. Texts, visual documentation and a poem enter into dialogue with each other, offering the reader a sort of exhibition on the page. An invitation to reflect on our entanglements with external realities. In an age of ecological derangement, major geopolitical shifts, and 24/7 neoliberal regimes, the present is a time of complex global transformations. Through their manifold effects, this only becomes manifest and experienceable by the individual on the local level. While the transformations seem to be mainly taking place outside and around us, their effects constantly point at us, questioning our anthropocentric, western and westernized perspectives, until they reveal the role of our human agency--as a species as well as individuals--within them and within our environment at large. Today, we find ourselves in the middle of a transition that does not present itself as a process of overcoming or as the production of the new in avant-garde fashion, but rather as a process demanding that we reinterpret the past and redefine our present (which is characterized by a still incomplete paradigm shift). Art is an open system that feeds on exchange. Through the work of many contemporary artists, art nowadays becomes the expression of a world that is shared with non-human entities and beings. This offers more intimate perspectives and understandings of our entanglements within the transformations of our uncertain times. Gazing through various apertures of Sketches of Transition's featured researches, each chapter could be considered a sketch of transition in itself, as an annotation on an alternative perspective on the material and visual spheres of our existences. With the same freedom of sketching on a blank paper sheet, the contributions investigate and probe new modes of production of beauty and wonder."--Publisher information.